Hepatic Aryl hydrocarbon Receptor Nuclear Translocator (ARNT) regulates metabolism in mice - Scott, Christopher H. (PLoS One, 2017)
BACKGROUND & AIMS: Aryl hydrocarbon Receptor Nuclear Translocator (ARNT) and its partners hypoxia-inducible factors (HIF)-1α and HIF-2α are candidate factors for the well-known link between the liver, metabolic dysfunction and elevation in circulating lipids and glucose. Methods: Hepatocyte-specific ARNT-null (LARNT), HIF-1α-null (LHIF1α) and HIF-2α-null (LHIF2α) mice were created. RESULTS: LARNT mice had increased fasting glucose, impaired glucose tolerance, increased glucose production, raised post-prandial serum triglycerides (TG) and markedly lower hepatic ATP versus littermate controls. There was increased expression of G6Pase, Chrebp, Fas and Scd-1 mRNAs in LARNT animals. Surprisingly, LHIF1α and LHIF2α mice exhibited no alterations in any metabolic parameter assessed. CONCLUSIONS: These results provide convincing evidence that reduced hepatic ARNT can contribute to inappropriate hepatic glucose production and post-prandial dyslipidaemia. Hepatic ARNT may be a novel therapeutic target for improving post-prandial hypertriglyceridemia and glucose homeostasis.